Public sector pay and adjustment : lessons from five countries - Colclough, Christopher (Routledge, 1997)
Case studies of Singapore, Korea, Zambia, Zimbabwe and Argentina show that in those countries which adjusted unsuccessfully real earnings declined sharply, often with a further negative impact on output.
Keywords: Developing countries -- Officials and employees -- Salaries, etc. -- Case studies.; Structural adjustment (Economic policy) -- Developing countries -- Case studies.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Employees -- Salaries, etc.; Structural adjustment (Economic policy); Developing countries; Ambtenaren.; Salarissen.; Ontwikkelingslanden.; Electronic books.; Case studies